Implementation of the Rights of the Child at the Level of ECEC Institutions: Policies and Practices in North Macedonia - Tasevska, Alma (Springer International Publishing, 2021)
To implement the recommendations of the UN Committee on the Rights of the Child (CRC), the Government in North Macedonia adopted a decision establishing a National Commission and drafting the National Action Plan on Children’s Rights. Significant activities of the Commission which should be implemented according to the National Action Plan on Children’s Rights are the following: Initiative for amendments to the Law on Trade and the Law on Catering Activity; Preparation of a brochure on children’s rights: Creating a simulative environment and providing an open floor for talking to children about their rights (for pre-school aged children which are part of the ECEC institutions, and for I, II and III grade primary school children), which the Commission published and distributed to all ECEC institutions. From the aspect of the practice, ECEC institutions have the opportunity to create their own program which can increase the capacities for implementation of the United Nation’s convention on the rights of the child. With a view to enhancing the trust and advancing the cooperation between the Government, ECEC institutions and citizen’s associations, the Strategy on Cooperation was adopted, accompanied with an Implementation Action Plan. The Strategy sets forth seven mutually connected strategic goals, which support the cooperation with, and the development of the civil sector. Participation of the civil sector in the policy design is an especially important area in this respect.
Keywords: young children, children’s rights, ECEC institutions, policies and practices